2011
DOI: 10.1002/zoo.20425
|View full text |Cite
|
Sign up to set email alerts
|

Visitor Effects on the Behavior of Captive Western Lowland Gorillas: The Importance of Individual Differences in Examining Welfare

Abstract: Given the conflicting and somewhat limited findings available on the effect of zoo visitors on primate behavior, the primary purpose of this study was to provide additional data on gorillas' response to variations in crowd size and to look at what other factors-both intrinsic (e.g. personality, sex, and rearing history) and extrinsic (e.g. group)-might influence such responses. Subjects included four groups (three mixed-sex and one bachelor) of captive western lowland gorillas living at Zoo Atlanta. Overall ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
100
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 31 publications
6
100
3
Order By: Relevance
“…Human impact studies have typically been limited to the effect of unfamiliar visitors on primates' behavior and wellbeing [Davey, 2007;Fernandez et al, 2009;Hosey, 2000Hosey, , 2008 and have often drawn wellbeing conclusions based on data pooled across primate species [e.g., Chamove et al, 1988;Hosey, 2000;Hosey & Druck, 1987;Mitchell et al, 1992]. Recent work suggests that visitor effect studies (VES) may not capture the full range of primate-human interactions in the zoo and suggest the need to explore individual or species behavior differences [Hosey, 2008;Kuhar, 2008;Stoinski et al, 2011]. Specifically, VES may be improved or extended by (1) considering humans other than unfamiliar visitors, (2) considering primates' social initiatives rather than or in addition to their responses to humans, and (3) considering potential differences prior to pooling species data to draw conclusions regarding humannon-human primate interaction and visitor effects.…”
Section: Introductionmentioning
confidence: 98%
“…Human impact studies have typically been limited to the effect of unfamiliar visitors on primates' behavior and wellbeing [Davey, 2007;Fernandez et al, 2009;Hosey, 2000Hosey, , 2008 and have often drawn wellbeing conclusions based on data pooled across primate species [e.g., Chamove et al, 1988;Hosey, 2000;Hosey & Druck, 1987;Mitchell et al, 1992]. Recent work suggests that visitor effect studies (VES) may not capture the full range of primate-human interactions in the zoo and suggest the need to explore individual or species behavior differences [Hosey, 2008;Kuhar, 2008;Stoinski et al, 2011]. Specifically, VES may be improved or extended by (1) considering humans other than unfamiliar visitors, (2) considering primates' social initiatives rather than or in addition to their responses to humans, and (3) considering potential differences prior to pooling species data to draw conclusions regarding humannon-human primate interaction and visitor effects.…”
Section: Introductionmentioning
confidence: 98%
“…This important area of work includes many more studies than those reviewed here (e.g. There has also been considerable debate regarding the effect of zoo visitors on animal behavior and welfare, with some studies reporting neutral or positive effects and others reporting behavior indicative of increased stress (Claxton, 2011;Davey, 2007;Farrand, Hosey, & Buchanan-Smith, 2014;Fernandez, Tamborski, Pickens, Timberlake, 2009;Hosey, 2000Hosey, , 2005Kuhar, 2008;Ross, Londsdorf, Stoinski, 2007;Smith & Kuhar, 2010;Stoinski, Jaicks, Drayton, 2012;Wells, 2005). Davey (2007) suggested that more study is needed before strong conclusions may be drawn, and called on zoo staff to monitor stress indicators in animals as a means of assessing visitor effects at specific exhibits.…”
Section: Enrichment Goals Strategies and Measuresmentioning
confidence: 99%
“…Davey (2007) suggested that more study is needed before strong conclusions may be drawn, and called on zoo staff to monitor stress indicators in animals as a means of assessing visitor effects at specific exhibits. Similarly, Kuhar (2008) and Stoinski et al (2012) emphasized the importance of monitoring visitor effects on individual animals after finding inconsistent affects among several groups of gorillas. Fernandez et al (2009) provided some specific and testable recommendations (involving zoo staffing, exhibit design, and enrichment strategies) for balancing the need to generate visitor interest with the potential adverse impacts of large crowds on animal welfare.…”
Section: Enrichment Goals Strategies and Measuresmentioning
confidence: 99%
“…Visitor numbers and active, noisy crowds exacerbate the negative effects on primates (e.g., Birke, 2002;Cooke & Schillaci, 2007;Keane & Marples, 2003;. However, some visitor effect studies had conflicting results between the same species at different locations (Carder & Semple, 2008;Stoinski, Jaicks, & Drayton, 2012). The option to move away from visitors may be an important reason for these discrepancies, with "choice and control" being identified as potentially important components in visitor effect studies (Smith & Kuhar, 2010, p. 160).…”
mentioning
confidence: 96%
“…Recently, studies tend to focus on the aspects of visitors (e.g., noise, gender, and height) that are disturbing to zoo-housed animals. Additionally, the zoo setting-such as husbandry routines, enclosure design, and weather conditions, as well as individual animal characteristics, including an animal's ability to habituate to the zoo settingsshould be considered (Hosey, 2005;Stoinski et al, 2012). However, one aspect of the zoo setting that has been completely overlooked is the presence of zoo playgrounds and their potential effect on animals housed nearby.…”
mentioning
confidence: 98%